KAJIAN SEMANTIK: ANALISIS MAKNA LEKSIKAL PADA LIRIK LAGU “ALAMAK” KARYA RIZKY FEBIAN DAN ADRIAN KHALIF - Eva Berliana (Jurnal Manajemen Pendidikan, 2025)
This study aims to describe the forms and lexical meanings contained in the lyrics of Alamak by Rizky Febian and Adrian Khalif using a semantic approach. This research employs a qualitative descriptive method, focusing on a deep interpretation of word meanings based on the lyrical context without involving statistical calculations. The primary data are taken from the lyrics of Alamak, while the secondary data are obtained from various literature sources such as books, journals, and previous studies relevant to semantic analysis. The data were collected using the observation and note-taking techniques and then analyzed using theory of semantics. The results of this study show that there are 13 data points of lexical meaning found in the lyrics of Alamak. Among them, there are 6 instances of repetition, 3 instances of synonymy, and 4 instances of antonymy. Repetition is used to emphasize the songwriter’s emotional expression and to illustrate the intensity of deep love. Synonymy enriches the expression of love without losing its poetic nuance, while antonymy serves to highlight the contrast of meanings that reflect the inner conflict between happiness and suffering. It can be concluded that the lexical meanings in Alamak function not only as a means of aesthetic expression but also as a medium of psychological revelation that reflects dynamics human emotion in the context of love.